Godfatherism, clientelism and violence: a chronology of gubernatorial elections in Oyo State Nigeria, 1999-2015 / Adebiyi and Oluwashina Moruf - A, Adebiyi; Moruf, Oluwashina (Universiti Teknologi MARA, 2021)
Electoral politics in new democracies of Africa have been largely defined by the phenomena of godfatherism, clientelism and violence. The right bestowed on the people by democracy to choose who represents them in free and fair elections has been eroded by godfather politics which usually manifests through clientelism and often enforced by violence. While studies have shown that these phenomena have far reaching implications on the electoral and democratisation processes of African nations, most of the studies approached the phenomena from the national perspective, paying little attention to how they manifest at the sub-national or state levels. This article is an empirical exploration of the manifestations of these phenomena in gubernatorial elections in Oyo state from 1999 to 2015. The research design is qualitative. Data were derived from primary and secondary sources. Through the purposive sampling technique, primary data were collected using Key Informant and in-depth interviews and Focus Group Discussions. Secondary data were derived from extant relevant literature. Data were analysed using content analysis. Findings revealed that the violent nature of gubernatorial elections in the state in the period of study was largely due to Chief Lamidi Adedibu's clientelist and patronage politics branded by violence and political thuggery. The study concludes that the implications include: bad leadership, corruption, impunity and increased criminal activities which have impacted negatively on government policies in the state.